PENENTUAN KRITERIA PENILAIAN KESAN JUMLAH TROMBOSIT PADA PEMERIKSAAN APUSAN DARAH TEPI - Aan Yulianingsih Anwar; Nurhamsiah (Jurnal Kesehatan Panrita Husada, 2018)
Platelets are one of the blood components present in the human body, which play an important role in hemostasis. A good macroscopic and microscopic peripheral blood smear is essential in assessing success in the manufacture of peripheral blood smear preparations. This research was conducted on March, 9thto May, 31st2018 at Hematology Laboratory of Health Polytechnic of Makassar majoring in Health Analyst. The purpose of this study to determine the number of thrombocytes view ability and declared the impression of sufficient quantities. The type of research used in this study is laboratory observation that aims to determine the assessment criteria impression of the number of platelets in the peripheral blood smear. The results showed that the number of platelets in zone I obtained results the impression of the number of platelets 5-9 stated the amount of normal platelet impression, zone II obtained the result total number of platelets impression 6-10 stated the amount of normal platelet impression, and the impression of the results obtained III zone number of platelets 7-11 stated the number of the impression of normal platelets. Therefore, advisable to the laboratory to calculate the platelet count using the peripheral blood smear method by counting at zone II and in subsequent studies it is better to examine the difference in platelet counts in each zone in the peripheral blood smear.